Coupled Analysis of Heat Transfer in a Molten Pool With Three-Layer Configuration - Deng, Jian; Zhu, Dahuan; Luo, Yuejian; Sun, Hongping; Zhang, Ming; Liu, Lili; Xiang, Qingan; Wu, Xiaoli; Xu, Youyou; Xiong, Qingwen (Frontiers in Energy Research, 2022)
Understanding reliable description of the heat transfer in molten pool with three layers configuration is inevitable for the design of severe accident mitigation measures in research reactors, such as IVR-ERVC. However, investigations on thick lower metallic layer are scarce. Thus, further studies on heat transfer in molten pool with thick lower metallic layer are highly required, based on previous severe accident studies in light water reactors. This paper conducts numerical simulation of heat transfer in molten pool with thick lower metallic layer during severe accident, combining model development, code verification, and code application. Firstly, MPCAP code has been develop, based on the coupled simulation of natural convection inside molten pool, two-dimensional heat conduction in RPV lower head and convection outside reactor vessel wall. Then, a verification case has been conducted using three layers configuration in AP1000. The AP1000 verification case indicates that MPCAP code predicts important parameters in molten pool well.